Territory, Hilāl, and Sovereignty: Revisiting Indonesia’s Maṭla’ under MABIMS’ New Criteria - Arisafitri, Novi; Imron, Ali; Syifaul Anam, Ahmad; Darliswanto (Fakultas Syari'ah dan Hukum UIN Walisongo, 2025)
Differences in determining the start of the lunar month often spark polemics due to varying methods, schools of thought, and interpretations of maṭla’. Indonesia adopts a territorial-based maṭla’, yet inconsistencies remain in how its geographical boundaries are applied. Law No. 43/2008 defines Indonesia’s territory as including land, sea, and air, raising questions about the ideal scope of maṭla’ under the MABIMS Neo Visibility Criteria and its legal status. This qualitative study uses library research and expert interviews, analyzed through Islamic legal principles (ijtihād istiṣlāhī) and a juridical-normative framework. Findings show that Indonesia’s maṭla’ ideally includes all sovereign areas-land, inland waters, archipelagic waters, and territorial seas. From a syar’i perspective, crescent sightings at sea are valid; hence, lunar calculations should reflect land and maritime zones under national jurisdiction.